Isolasi dan Karakterisasi Jamur Endofit Daun Belimbing Hutan (Cnestis palala (Lour.) Merr): Isolation and Characterization of Endophytic Fungi from Leaves of (Cnestis palala (Lour.) Merr) - Nurvidya Sistha Azzahra; Nisa Naspiah; Lizma Febrina (Proceeding of Mulawarman Pharmaceuticals Conferences, 2023)
Belimbing hutan (Cnestis palala (Lour.) Merr) is recognized as a distinctive plant in East Kalimantan, commonly used by the local community for treating internal diseases, postpartum conditions, abdominal pain, and urinary tract disorders. The benefits of belimbing hutan cannot be separated from the compounds contained in it. However, the limited population makes exploration of this plant hampered. Endophytic fungi are an interesting alternative for exploring secondary metabolites from this plant. To date, there have been no scientific reports on endophytic fungus of belimbing hutan. This research successfully isolated and characterized three isolates from the leaves of belimbing hutan with isolate codes IJP1 exhibiting white colonies with a cotton-like texture, IJP2 colonies are white and fiber-shaped, IJH1 with green colonies accompanied by concentric circles. The diversity of endophytic fungi in belimbing hutan leaves opens up possibilities for discovering potential compounds from the extracts of these fungi. Keywords: Cnestis palala (Lour.) Merr, Endophytic Fungi, Isolation, Characterization Abstrak Belimbing hutan (Cnestis palala (Lour.) Merr) dikenal sebagai tanaman khas Kalimantan Timur yang umumnya digunakan sebagai obat penyakit dalam, obat pasca melahirkan, sakit perut dan gangguan saluran kemih oleh masyarakat sekitar. Khasiat dari belimbing hutan ini tidak terlepas dari senyawa yang terkandung di dalamnya. Namun, populasi yang terbatas membuat eksplorasi tumbuhan ini menjadi terhambat. Jamur endofitik merupakan salah satu alternatif menarik untuk mengeksplorasi metabolit sekunder dari tanaman ini. Sepanjang pengetahuan, belum ada laporan ilmiah mengenai jamur endofitik belimbing hutan. Penelitian ini berhasil mengisolasi dan mengkarakterisasi tiga isolat dari daun belimbing hutan dengan kode isolat IJP1 yang memiliki karakteristik koloni berwarna putih dan tekstur halus seperti kapas, IJP2 koloni berwarna putih dan berbentuk serabut, IJH1 koloni berwarna hijau disertai lingkaran konsentris. Beragamnya jamur endofitik daun belimbing hutan membuka peluang ditemukannya senyawa potensial dari ekstrak jamur endofitik daun belimbing hutan. Kata Kunci: Cnestis palala (Lour.) Merr, Jamur Endofit, Isolasi, Karakteristik